Water and electrolyte needs for football training and match-play - Shirreffs, S. M.; Sawka, N. M.; Stone, M. (Journal of Sports Sciences, 2006)
The high metabolic rates sustained by soccer players during training and match-play cause sweat to be produced in both warm and temperate environments. There is limited published information available on the effects of this sweat loss on performance in soccer. However, this limited information, together with knowledge of the effects of sweat loss in other sports with skill components as well as endurance and sprint components, suggests that the effects of sweating will be similar to the effects in these other activities. Therefore, the generalization that a body mass reduction equivalent to 2% should be the acceptable limit of sweat losses seems reasonable. This amount, or more, of sweat loss reflected in body mass loss is a common experience for some players. Sodium is the main electrolyte lost in sweat and the available data indicate considerable variability in sodium losses between players due to differences in sweating rate and sweat electrolyte concentration. Additionally, the extent of sodium loss is such that its replacement will be warranted for some of these players during training sessions and matches. Although soccer is a team sport, the great individual variability in sweat and electrolyte losses of players in the same training session or match dictates that individual monitoring to determine individual water and electrolyte requirements should be an essential part of a player's nutritional strategy.